Proses Painting dan Pengukuran Ketebalan Cat Pada Kabin Mobil Type Dutro Dump 130 HD X-POWER di PT. XYZ - Aang Iryadi; Rizal Hanifi; Kardiman; Viktor Naubnome (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The process of painting a car cabin at PT XYZ, a leading automotive company in Indonesia, involves a series of structured and rigorous steps to ensure optimal paint quality before the vehicle leaves the manufacturing facility. The painting process involves a series of structured stages, starting from surface preparation to application of paint layers. Paint thickness measurements are carried out to ensure that the thickness of the paint layer complies with established standards for optimal protection and aesthetics. It was found that the company implemented advanced technologies such as electrodeposition (ED) to ensure an even and long-lasting paint layer. Apart from that, implementing grounding safety and the Quality Gate process is key in maintaining safety, quality and customer satisfaction